2020
DOI: 10.3390/microorganisms8101522
|View full text |Cite
|
Sign up to set email alerts
|

Culturing Ancient Bacteria Carrying Resistance Genes from Permafrost and Comparative Genomics with Modern Isolates

Abstract: Long considered to be a consequence of human antibiotics use by deduction, antibiotic resistance mechanisms appear to be in fact a much older phenomenon as antibiotic resistance genes have previously been detected from millions of year-old permafrost samples. As these specimens guarantee the viability of archaic bacteria, we herein propose to apply the culturomics approach to recover the bacterial content of a Siberian permafrost sample dated, using the in situ-produced cosmogenic nuclide chlorine36 (36Cl), at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Finally, it is also possible that these genes are naturally present within Siberian bacteria as a response to naturally produced antibiotic-like compounds. Antibiotic-resistant genes have now been reported in various soil samples from Arctic and Antarctic regions, including millions-year-old permafrost, i.e., these genes originate from the pre-antibiotic era in medicine [24,62,71,72]. Detection of antibiotic resistance genes in bacterial species recovered from permafrost indicates that antibiotic resistance predates humanity and these are natural resistance mechanisms to antimicrobial agents produced and used by microorganisms as weapons in intermicrobial competition within the biosphere [72].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is also possible that these genes are naturally present within Siberian bacteria as a response to naturally produced antibiotic-like compounds. Antibiotic-resistant genes have now been reported in various soil samples from Arctic and Antarctic regions, including millions-year-old permafrost, i.e., these genes originate from the pre-antibiotic era in medicine [24,62,71,72]. Detection of antibiotic resistance genes in bacterial species recovered from permafrost indicates that antibiotic resistance predates humanity and these are natural resistance mechanisms to antimicrobial agents produced and used by microorganisms as weapons in intermicrobial competition within the biosphere [72].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the search for antibiotic resistance genes in microorganisms that have not previously come into contact with the human population is of great interest [ 12 ]. Many studies on permafrost have reported the presence of genes coding for resistance to several classes of antibiotics [ 13 , 14 , 15 , 16 , 17 , 18 ] and heavy metals [ 19 , 20 ] similar to ones observed in present day clinical and environmental strains. The Psychrobacter maritimus strain, resistant to tetracycline and streptomycin, was isolated from 15,000–35,000 years old permafrost sediments sampled from the coast of the East Siberian Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Perron et al used functional metagenomics to retrieve antibiotic resistance genes from bacteria isolated from Canadian high Arctic permafrost and identified genes conferring clinical levels of resistance against aminoglycoside, β-lactam and tetracycline antibiotics [ 17 ]. Twenty eight bacterial species were cultured form a Siberian permafrost sample dated at 2.7 million years and resistance to antibiotics was phenotypically detected in all 10 Gram-negative species [ 18 ]. No significant differences in antibiotic resistance profiles between modern and ancient isolates of each species were found [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation